Digital Infographic Creation in Design Education: A Participatory Learning Algorithm Measuring Location-Based Spatial Impact - Birer, Emel; Hasgül, Esin; METİN, ELİF GİZEM (Wiley, 2025)
Design education includes many pursuits that deal with creativity, thinking and visual communication techniques in the learning process. This study aims to create a participatory learning algorithm based on a location, while measuring the spatial impact through an emergent situation. The exemplified issue is determined as fire that emerged due to climate change, which has become a significant agenda of the 21st century in most countries. The scope of the study is based on the creation of an algorithm for participatory learning techniques by using social media to create digital infographics in a workshop redefining Mugla, an affected place after the fire. The workshop context is designed to reveal the interaction between humankind and its natural environment, including nature, topography, animals, aids and all actors affected after the fire, while students are involved in research practices on participatory learning, using the diary method as a pedagogical research tool. The outputs of the participatory learning algorithm examine the informative part of the produced digital infographics with ethnomethodology and the visual part with descriptive analysis as a hybrid methodology taking data materials from social media. Cumulative results that reflect the location-based spatial impact are measured with a coding system of frequencies and a time-series data of polar mapping. We propose that such a participatory learning algorithm can improve students' visual communication, design creation, visualisation, expression of ideas and organisation of knowledge skills with the discipline of working together to make multilayered spatial readings.
Keywords: Design Education; Infographics; Participatory Learning; Spatial Impact; Time-series Data